2015
DOI: 10.3174/ajnr.a4235
|View full text |Cite
|
Sign up to set email alerts
|

Quiet PROPELLER MRI Techniques Match the Quality of Conventional PROPELLER Brain Imaging Techniques

Abstract: BACKGROUND AND PURPOSE:Switching of magnetic field gradients is the primary source of acoustic noise in MR imaging. Sound pressure levels can run as high as 120 dB, capable of producing physical discomfort and at least temporary hearing loss, mandating hearing protection. New technology has made quieter techniques feasible, which range from as low as 80 dB to nearly silent. The purpose of this study was to evaluate the image quality of new commercially available quiet T2 and quiet FLAIR fast spin-echo PROPELLE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…A recent study assessed the noise level of silent and conventional PROPELLER T 2 W sequences on a clinical 1.5-T MR imaging system, similarly obtaining 26.4 dB noise reduction. 7 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent study assessed the noise level of silent and conventional PROPELLER T 2 W sequences on a clinical 1.5-T MR imaging system, similarly obtaining 26.4 dB noise reduction. 7 …”
Section: Discussionmentioning
confidence: 99%
“…Previous reports for the adult population on a 1.5-T MR imaging system showed that quiet T 2 W and T 2 FLAIR images were comparable in image quality with conventional acquisitions. 7 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They also apply a degree of gradient derating that results in longer gradient rise time (i.e., reduced slew rate) in conjunction with lower readout bandwidth, which then results in reduced readout gradient amplitudes, in turn reducing the Lorentz forces. Robust noise reduction has been demonstrated at 1.5 to 4T MRI with gradient echo (13,14,17), fast spin echo/turbo spin echo (13,14,18), and even multiecho gradient echo readouts (19). Applying the same techniques in EPI, however, has proved to be more challenging because it is louder to begin with, and because derating inevitably further reduces the phase-encoding bandwidth, aggravating the severe image distortion (20).…”
Section: Introductionmentioning
confidence: 99%